ANALYSIS OF DYNAMIC LOADS ON A MULTI-STOREY BUILDING WITH THE LIRA PROGRAM (Spectrum Journal of Innovation, Reforms and Development, 2023)
The article identifies the state of displacement and deformation of the roof of a 12-storey hotel building under construction in Khorezm region as a result of unusual loads and seismic effects during the helicopter landing.